2022
DOI: 10.3390/plants11111498
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of MDH Family Genes and Their Association with Salt Tolerance in Rice

Abstract: Malate dehydrogenase (MDH) is widely present in nature and regulates plant growth and development, as well as playing essential roles, especially in abiotic stress responses. Nevertheless, there is no comprehensive knowledge to date on MDH family members in rice. In this study, a total of 12 MDH members in rice were identified through genome-wide analysis and divided into three groups on the basis of their phylogenetic relationship and protein-conserved motifs. Evolutionary analysis showed that MDH proteins fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Seven SgMDHs were found in stylosanthes, and subcellular localization showed that SgMDH mainly ex-ists in the cytoplasm, chloroplasts, peroxidase bodies, and vacuolar membranes [18]. In addition, 12 OsMDHs have been confirmed in O. sativa [15], and 12 SlMDHs have also been verified in tomato (Solanum lycopersicum) [17]. Twenty MpMDHs have been identified in the whole genome of apple (Malus pumila) [18], and studies have shown that the number of MDHs is different in different species of plants and that the MDHs are distributed in different subregions of plant cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Seven SgMDHs were found in stylosanthes, and subcellular localization showed that SgMDH mainly ex-ists in the cytoplasm, chloroplasts, peroxidase bodies, and vacuolar membranes [18]. In addition, 12 OsMDHs have been confirmed in O. sativa [15], and 12 SlMDHs have also been verified in tomato (Solanum lycopersicum) [17]. Twenty MpMDHs have been identified in the whole genome of apple (Malus pumila) [18], and studies have shown that the number of MDHs is different in different species of plants and that the MDHs are distributed in different subregions of plant cells.…”
Section: Discussionmentioning
confidence: 98%
“…With the development of bioinformatics technology, an increasing number of MDH members have been authenticated in plants, such as Oryza sativa [15], Glycine max [45], and Stylosanthes guianensis [18]. Eight MDH genes in beans (Phaseolus vulgaris) have been identified and found to be mainly located in the cytoplasm and chloroplasts [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity of gene function within branches of a multi-species phylogenetic tree has been verified [ 66 ]. By analyzing the phylogenetic relationships and collinear analysis of ginger and four other plant HSF members, we can make initial predictions about the function of ZoHSF members in response to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…AI can identify relevant biomarkers and recognize complex patterns from various data types in responses to stress, pinpointing regulatory hubs within gene networks, proteins complexes or epigenetic modifications pivotal to plant stress responses, as well as determining interactions among the different regulatory levels mediating plant adaptation to stress (Crandall et al, 2020; Zhang et al, 2022).…”
Section: Possible Role Of Multi‐omics and Artificial Intelligence To ...mentioning
confidence: 99%